Influence of different spacings, SNP concentrations and sources of nitrogenous fertilizer on the total carotenoids content in African marigold - DHULIPALLA, APARNA; BHASKAR, V. VIJAYA; P. SUBBARAMAMMA (Journal of Ornamental Horticulture, 2024)
A factorial experiment with three different spacings, three different concentrations of sodium nitroprusside (SNP) and three different sources of nitrogenous fertilizer was conducted during summer months for two years i.e., 2017 and 2018 at the Horticultural Research Station, Dr. Y.S.R. Horticultural University, Venkataramannagudem to find out their influence on the total carotenoids content of marigold flower petals cv. 'Bidhan-2'. The results have revealed that wider spacing adopted at 60 cm × 30 cm (1.37, 1.40 and 1.39 g kg–1 petals of FW), foliar application of SNP at higher concentration of 200 µM (1.55, 1.59 and 1.57 g kg–1 petals of FW) and soil application of nitrogen in the form of calcium nitrate @ 581 kg ha–1 (1.41, 1.45 and 1.43 g kg–1 petals of FW) recorded significantly highest total carotenoids content during the 1st year, 2nd year and the pooled data mean, respectively. Among the two combination treatments, flowers obtained at a spacing of 60 cm × 30 cm in combination with higher concentration of SNP @ 200 µM recorded significantly higher total carotenoids content in the flower petals of marigold followed by soil application of calcium nitrate in combination with either of the concentrations of SNP. Among the three combination treatments, flowers obtained at a spacing of 60 cm × 30 cm and foliar application of SNP @ 200 µM concentration in combination with soil application of Ca(NO3)2 recorded significantly highest total carotenoids content (1.70 g kg–1 petals of FW) in marigold cultivated during summer.